Status of Psychological Adjustment and Associated Factors in Patients with Type 2 Diabetes in Zanjan University of Medical Sciences - 2019 - Fatemeh Bahramy; Masoumeh Namadian; Mehran Nezamdiba; Zeinab Ghahremani (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Diabetes is one of the major health issues worldwide and a challenge for health care providers. Objectives: The aim of this study was to determine the status of psychological adjustment and associated factors in patients with type 2 diabetes in Zanjan University of Medical Sciences. Methods: This descriptive cross-sectional study was carried out on 350 patients with type 2 diabetes referred to Vally-e-Asr Medical Center in Zanjan and Special Endocrinology Clinic in 2019. These patients were included in the study by the Poisson distribution method. Demographic and clinical factors questionnaires and valid Diabetes Adjustment Assessment Scale (DAAS) were used in this study. Data analysis was conducted using SPSS22 software. Also, Pearson correlation coefficient, independent t-tests, and analysis of variance were applied. Results: The mean of total adjustment in this study was 162.79± 18.06. The highest mean of adjustment was related to advanced self-management (4.15± 0.84) and the lowest mean of adjustment was about the initial imaging of illness (3.23± 0.67). Patients' adjustment had a statistically significant relationship with hospitalization history, family history of diabetes, HbA1C level, history of physical, psychological, and social problems caused by diabetes, place of residence, marital status, education, occupation, age, duration of illness, and income. Conclusion: In this study, patients had an acceptable adjustment. Because adjustment varies among individuals and is influenced by demographic, clinical, and social factors, it is recommended that diabetic caregivers include individual-oriented diabetes education and promotion of adjustment to the disease in their program.